Study on the Relationship between Wheat Flour Quality Characteristics and Processing Quality of Leavened Pancake - LI Yi; TIAN Xiao-hong; WANG Jia-ya; JIANG Ping; TAN Bin (Liang you shipin ke-ji, 2024)
In order to select suitable wheat flour raw materials for industrial processing of dough, 12 wheat varieties with a wet gluten content of 24.4%~32.7% were selected. The physicochemical properties, flour properties, viscosity properties, and fermentation rheological properties of wheat flour were measured, and the correlation between wheat flour properties and dough quality was analyzed. The results showed that as the wet gluten content increased, the fermentation height, total volume, retention coefficient (R), and specific volume of the dough all increased (P<0.05). The maximum shear force of dough showed a trend of first increase and then decrease, while the sensory evaluation score showed a trend of first decrease and then increase. Through correlation analysis, it was found that the wet gluten content, peak viscosity, minimum viscosity, final viscosity, retrogradation value, peak time, flour quality index, maximum fermentation height (Hm), and final fermentation height (h) of flour were significantly positively correlated with the specific volume of the dough, while the starch content and gluten index were negatively correlated with the specific volume of the dough. The starch and protein content of flour were negatively correlated with the maximum shear force of dough, while the wet gluten content was positively correlated with the maximum shear force of dough. Wheat flour with a gluten content of 30.0%~33.0%, a gluten index of 70~78, a flour index of 58.5~ 69.5, an Hm of 38.1~55.1 mm, and an R of over 95% could be more suitable for making leavened pancakes.